The Influence of Brand Image on Consumer Satisfaction of Make Over Cosmetics in STIE Amkop Makassar Students - Amar Sani (SEIKO : Journal of Management & Business, 2023)
The purpose of this study is to identify and analyze how brand image affects consumer satisfaction. This quantitative research involved 89 sample students and used the regression analysis technique of questionnaire data pathways. These results show that brand image (X) has a positive and significant influence on consumer satisfaction. This study also proves that the hypothesis is accepted that brand image has a positive and significant influence on consumer satisfaction. Kata Kunci: Brand Image, Customer Satisfaction